THE PERFORMANCE COMPARISON OF RF LEVEL MULTIPLEXING AND OPTICAL LEVEL MULTIPLEXING IN RADIO OVER FIBER SYSTEMS WITH DIRECT OPTICAL MODULATION TECHNIQUES - Febrizal Ujang; Adillah Putri; Esra Erianti; Hotnida Hannum; Putri Anisa (Lembaga Penelitian Universitas Pasundan, 2023)
Communication in the world is developing very rapidly, not only limited to voice but data communication. Many techniques have been used to support multimedia services. Radio over Fiber is expected to support communication for long distances. Therefore, a Comparison of Performance Analysis was carried out using optisystem. Radio over Fiber is simulated by radio frequency signals of 10 GHz and 15 GHz. Radio over Fiber technology for long-distance communication is very vulnerable to high BER and attenuation values, so it requires a mature system design and adequate equipment specifications.